2000
DOI: 10.1177/008124630003000302
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-Legal Issues Affecting Rape Survivors with Mental Retardation

Abstract: Rape survivors who are believed to have mental retardation are subjected to a somewhat different sequence of legal events compared to those without this disability. Their intellectual functioning is questioned, as is their competence to give evidence in the trial of the alleged perpetrator. The authors studied 10 such cases in terms of the contextual aspects of the rape, the survivors' cognitive functioning and their ability to provide accounts of the assaults. The findings indicated that although eight of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…For child witnesses whose more severe retardation would require giving testimony in a less conventional manner, these methods could be employed by attorneys generally, to their benefit. 62 It is interesting to note that the use of anatomically correct dolls and other props is the method most currently used to assist child witnesses with mental retardation to recall and communicate their testimony, and this method is also rated as being the most acceptable by participating attorneys. The use of such props assists the child witness with mental retardation who lacks command of sexual or anatomical knowledge or terminology to describe events and persons to the court.…”
Section: Discussionmentioning
confidence: 99%
“…For child witnesses whose more severe retardation would require giving testimony in a less conventional manner, these methods could be employed by attorneys generally, to their benefit. 62 It is interesting to note that the use of anatomically correct dolls and other props is the method most currently used to assist child witnesses with mental retardation to recall and communicate their testimony, and this method is also rated as being the most acceptable by participating attorneys. The use of such props assists the child witness with mental retardation who lacks command of sexual or anatomical knowledge or terminology to describe events and persons to the court.…”
Section: Discussionmentioning
confidence: 99%
“…She was unable to provide details of the rape. [1] In another study by Pillay, [14] 106 rape survivors were evaluated for possible mental retardation. Most (91.5%) were female, 21.7% were aged <16 years, and over two-thirds were from rural communities.…”
mentioning
confidence: 99%
“…Only a few recent studies [1,14,15,17] conducted on mentally retarded rape victims in SA could be located in the literature.…”
mentioning
confidence: 99%
“…[7] In South Africa (SA), the South African Police Service (SAPS) Crime Information Analysis Centre does not provide a separate report of sexual crimes against individuals with mental retardation. [8] According to Pillay and Sargent, [1] this lack of reporting and documentation makes it difficult to estimate the incidence of such crimes in SA, and may perpetuate society's denial of the existence of sexual abuse of individuals with mental retardation. Calitz, [9] however, reported an increase in the referrals of mentally retarded rape survivors to the Free State Psychiatric Complex (FSPC) in Bloemfontein, SA.…”
mentioning
confidence: 99%
“…Pillay and Sargent, [1] who evaluated ten rape victims with possible mental retardation, found that six of the eight survivors with mental retardation were able to provide a clear account of the alleged rape and were therefore considered able to give evidence in court with some support. Two of the rape survivors did not show mental retardation.…”
mentioning
confidence: 99%